Performance of the nontreponemal tests and treponemal tests on cerebrospinal fluid for the diagnosis of neurosyphilis: A meta-analysis - Xie, Jia-Wen; Wang, Mao; Zheng, Ya-Wen; Lin, Yong; He, Yun; Lin, Li-Rong (Frontiers in Public Health, 2023)
Background Nontreponemal and treponemal tests for analyzing cerebrospinal fluid to confirm the existence of neurosyphilis have been widely used, so we aim to evaluate and compare their performance on the cerebrospinal fluid in the diagnosis of neurosyphilis. Methods We conducted a systematic literature search on five databases and utilized a bivariate random-effects model to perform the quantitative synthesis. Results Nontreponemal tests demonstrated a pooled sensitivity of 0.77 (95% CI: 0.68–0.83), a pooled specificity of 0.99 (95% CI: 0.97–1.00), and a summary AUC of 0.97 (95% CI: 0.95–0.98). The pooled sensitivity, pooled specificity, and summary AUC of treponemal tests were 0.95 (95% CI: 0.90–0.98), 0.85 (95% CI: 0.67–0.94), and 0.97 (95% CI: 0.95–0.98), respectively. The pooled specificity of all nontreponemal tests varied minimally (ranging from 0.97 to 0.99), with TRUST (0.83) having a higher pooled sensitivity than VDRL (0.77) and RPR (0.73). Among all treponemal tests, EIA has outstanding diagnostic performance with a pooled sensitivity of 0.99 and a pooled specificity of 0.98. Conclusion Nontreponemal tests exhibited a higher pooled specificity, and treponemal tests exhibited a higher pooled sensitivity in diagnosing neurosyphilis on cerebrospinal fluid. TRUST may be a satisfactory substitute for VDRL. EIA is a prospective diagnostic tool that deserves further study in the future. Our study may be useful to clinical laboratories in selecting appropriate serological tests on the cerebrospinal fluid for the diagnosis of neurosyphilis.